1998
DOI: 10.1007/s004050050058
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the middle ear with high resolution computed tomography and superfine fiberoptic videomicroendoscopy

Abstract: Ten temporal bone blocks were dissected from fresh postmortem specimens from patients succumbing to diseases unrelated to the ears. A superfine fiberoptic videomicroendoscope (SFV) was introduced through the eustachian tube into the middle ear, and middle ear structures were visualized. The cadaver temporal bone blocks were also studied with high-resolution computed tomography (HRCT). When HRCT gave good results SFV did not succeed well and vice versa. However, SFV provided topographic anatomical information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
2
Order By: Relevance
“…Vergleichende Studien zeigen, dass die transpharyngeale Endoskopie überall dort Vorteile hat, wo die CT Schwächen aufweist und vice versa. Beide Verfahren werden daher als Ergänzung gesehen [60]. Indikationen für einen klinischen Einsatz stellen die 7Stenosenlokalisation sowie die 7Abklärung einer offenen Tube dar.…”
Section: Untersuchungsmethodenunclassified
“…Vergleichende Studien zeigen, dass die transpharyngeale Endoskopie überall dort Vorteile hat, wo die CT Schwächen aufweist und vice versa. Beide Verfahren werden daher als Ergänzung gesehen [60]. Indikationen für einen klinischen Einsatz stellen die 7Stenosenlokalisation sowie die 7Abklärung einer offenen Tube dar.…”
Section: Untersuchungsmethodenunclassified
“…Visibility seemed to be better in the cadaver study. It is possible that mucosa and 347 Identified Identification of the structure questionable structure questionable Epitympanum 22 0 6 4 Oval window 23 0 2 3 Round window 23 0 0 3 Tympanic sinus 25 0 0 3 Facial recess 2 0 0 3 Subiculum 0 0 0 3 blood circulation in the middle ear cavity absorbed the light, so the visibility in patients was not so good when compared to the cadaver study endoscopies [5,8]. However, the same angioendoscopes were used in the cadaver study and it is also evident that some number of fibers of the endoscopes were lost during the atresia study.…”
Section: Discussionmentioning
confidence: 98%
“…The results suggest that these technologies supplement each other. They also suggested that in such cases as external ear dysplasia combining these two modalities would improve diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported that, clinically, the use of fibrescopes is restricted because of the limited resolution from the small images produced, and they do not have an angled tip to help to inspect the undersurfaces of the tympanic membrane or the recesses of the middle ear [15]. Karhuketo et al [27] compared the use of fibre-optic video-micro-endoscopy through the eustachian tube into the middle ear in ten dissected temporal bone blocks with the results of high-resolution computed tomography of the same temporal bones. These authors reported that, when high-resolution computed tomography gave good results, fibre-optic video-micro-endoscopy did not succeed well and vice versa.…”
Section: Discussionmentioning
confidence: 99%